2014
DOI: 10.1007/s11095-014-1473-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Skin Barrier Function Using Bioengineering and Biophysical Techniques

Abstract: Purpose: To characterise skin barrier function in vivo at two distinct anatomic sites using minimally invasive bioengineering and biophysical tools.Methods: In healthy human volunteers, the quantities of stratum corneum (SC) per unit area of skin on the forearm and forehead were quantified by gravimetric and imaging techniques. Organisation of the SC intercellular lipids was evaluated as a function of position using attenuated total reflectance infrared spectroscopy (ATR-IR). The constituents of natural moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…Although facial SC contains significantly lower levels of NMF compared with other body sites, we have shown that there are no differences in PCA levels between the cheek and PA sites [5,6,29]. However, UV irradiation is known to increase the expression of filaggrin and transglutaminase in mouse skin [36,37].…”
Section: Discussionmentioning
confidence: 96%
“…Although facial SC contains significantly lower levels of NMF compared with other body sites, we have shown that there are no differences in PCA levels between the cheek and PA sites [5,6,29]. However, UV irradiation is known to increase the expression of filaggrin and transglutaminase in mouse skin [36,37].…”
Section: Discussionmentioning
confidence: 96%
“…Barrier function is the basic attribute of epidermis. It is affected by the lipid composition of epidermis . Ponec et al .…”
Section: Discussionmentioning
confidence: 99%
“…Barrier function is the basic attribute of epidermis. It is affected by the lipid composition of epidermis [33][34][35]. Ponec et al showed that reconstructed human epidermis models contained major epidermal lipid classes but deviated from native epidermis in some lipid components, including high ceramide 2, low ceramides 5 and 6, and ceramide 7 [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…A number of bioengineering methods have been employed for the detection of early signs of hand eczema in an occupational screening setting. Several of these methods are supposed to enable a standardized qualitative and quantitative evaluation of skin diseases or follow‐up evaluation of therapeutic success . However, the comparisons of bioengineering methods such as TEWL and colorimetry during occupational screenings with the Hand Eczema Score for Occupational Screenings (HEROS) revealed only moderate accuracy concerning the estimation of disease severity, especially in the early stages of hand eczema …”
Section: Introductionmentioning
confidence: 99%
“…Several of these methods are supposed to enable a standardized qualitative and quantitative evaluation of skin diseases or follow-up evaluation of therapeutic success. [7][8][9] However, the comparisons of bioengineering methods such as TEWL and colorimetry during occupational screenings with the Hand Eczema Score for Occupational Screenings (HEROS) revealed only moderate accuracy concerning the estimation of disease severity, especially in the early stages of hand eczema. 10 As virtually all relevant skin changes are accompanied by erythema, several procedures were tested for the quantification of erythema in the past.…”
Section: Introductionmentioning
confidence: 99%